2013
DOI: 10.1140/epjp/i2013-13088-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of f(G) gravity with the new agegraphic dark-energy model

Abstract: In this work, we consider the reconstruction scenario of new agegraphic dark energy (NADE) model and f (G) theory of gravity with G representing the Gauss-Bonnet invariant in the flat FRW spacetime. In this context, we assume a solution of the scale factor in power-law form and study the correspondence scenario. A new agegraphic f (G) model is constructed and discussed graphically for the evolution of the universe. Using this model, we investigate the different eras of the expanding universe and stability with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In 2008, Kim et al [55] found that v 2 s for agegraphic DE is always negative which leads to classically instability of that model. Recently many researchers are using this methods to analyzed the stability of that models on which they worked and of which some authors [56,57,58,59] have reached to a conclusion that HDE, ADE, NADE, Chaplygin gas, holographic Chaplygin,…”
Section: Stability Analysismentioning
confidence: 99%
“…In 2008, Kim et al [55] found that v 2 s for agegraphic DE is always negative which leads to classically instability of that model. Recently many researchers are using this methods to analyzed the stability of that models on which they worked and of which some authors [56,57,58,59] have reached to a conclusion that HDE, ADE, NADE, Chaplygin gas, holographic Chaplygin,…”
Section: Stability Analysismentioning
confidence: 99%
“…We consider now the holographic cosmological model with IR cut-off given by the modified Ricci radius so that the corresponding energy density is a combination of H 2 andḢ [66][67][68], which reads…”
Section: The Mhrde Modelmentioning
confidence: 99%
“…Then, Chattopadhyay and Ghosh (2012) have explored the generalized second law of thermodynamics and pointed out that it holds in quintessence phase in F (R) gravity. We have also made correspondence of different modified theories of gravity with dynamical DE models and calculated different cosmological parameters (Jawad et al 2013a(Jawad et al , 2013b(Jawad et al , 2013c(Jawad et al , 2013dJawad 2014aJawad , 2014bJawad , 2014cJawad andRani 2015a, 2015b).…”
Section: Introductionmentioning
confidence: 99%